Parenting Patterns In Forming Children's Character in Rumah Bunda Karawang Daycare - Ardelia, Khalda; Arsal, Thriwaty (Universitas Tanjungpura, 2025)
This study analyzes the parenting patterns applied at Rumah Bunda Daycare and their contribution to children's character formation. In modern society, with increasing numbers of working parents, the reliance on childcare facilities like daycares has grown significantly, making their role in comprehensive child development a pressing concern. Employing a qualitative descriptive approach, this research focuses on children aged 2-5 years entrusted to the daycare. The findings indicate Rumah Bunda Daycare effectively creates an environment supporting children's physical, social, emotional, and cognitive development. Its parenting patterns are adapted to developmental stages, grounded in George Herbert Mead's socialization theory. The daycare also prioritizes children with special needs through an inclusive and personalized approach. Routine evaluations involving both parents and caregivers significantly improve parenting practices. Children in this program consistently show positive developments in independence, discipline, and and social skills. This study concludes that Rumah Bunda Daycare's parenting patterns play an important role in supporting children's overall growth and development.